Nobel the grand history of the Peace Prize - Stenersen, Oivind; Libaek, Ivar; Sveen, Asle (Whitman, 2014)
Alfred Nobel, the inventor of dynamite and the creator of the Nobel prizes, was a genius. The son of a self-taught Swedish master-builder, he had established 20 factories in Europe and the United States by the age of 40. Before his death in 1896, Nobel decided that most of his estate should be invested in securities and placed in a fund, the earnings to be "distributed in the form of prizes to those who, during the preceding year, shall have conferred the greatest benefits on mankind." One of the prizes, what we today call the Nobel Peace Prize, would be bestowed on the person who had "done the most of the best work for fraternity among nations, for the abolition or reduction of standing armies and for the holding and promotion of peace congresses." This fully illustrated book with vintage photographs provides you with an in-depth look at Alfred Nobel, the Nobel Peace Prize and the award's long and illustrious history.